Bioactivity of Nypa fruticans Leaves as A Candidate for Anticancer Compounds Against MCF-7 Breast Cancer Cells: Bioactivity of Nypa fruticans Leaves as A Candidate for Anticancer Compounds Against MCF-7 Breast Cancer Cells - Evy Noviana Noviana; Eva Johannes; Sjafaraenan (International Journal of Applied Biology, 2022)
Breast cancer is the highest incidence of cancer for among women worldwide. The use of anticancer compounds from natural ingredients as cancer therapeutics is to reduce chemotherapy side effects. Indonesia has high biodiversity especially its pharmacologically beneficial such as Nipah. Nipah (Nypa fruticans W.) is a type of palm-shaped mangrove plant which widely found in watershed areas . This study aims to explores the bioactivity of ethanol extract from N. fruticans leaves against MCF-7 breast cancer cells. Screening for bioactive compounds was performed by Gas chromatography-mass spectrometry (GC-MS). Anticancer pre-screening was assessed by brine shrimp lethality (BSL) test and anticancer activity was assessed by 3-(4,5-Dimethylthiazol-2-cyl)-2,5-Diphenyltetrazolium Bromide (MTT) assay. According of GC-MS analysis showed the presence of 54 phytochemical compounds. Some of them have bioactivity as anticancer including Sitosterol, Tocopherol, and Phytol. The BSLT method showed potent activity with LC50 was 84.25 µg/mL. Anticancer activity using MTT assays results the low IC50 value was 88.77 µg/mL that showed high anticancer activity by growth inhibition in MCF-7 breast cancer cells. This study delivers information that ethanol extract from N. fruticans leaves possesses bioactive compounds could be use as a candidate for anticancer compounds for cancer treatment.